PENGEMBANGAN MEDIA SAMMELNALBUM MENGGUNAKAN BARCODE UNTUK KETERAMPILAN MENYIMAK KALIMAT RUMPANG BAHASA JERMAN SISWA SMA KELAS XI - Widyanti Syndi Laurenzia,; Dra. Fahmi Wahyuningsih, M.Pd, (LATERNE, 2025)
The research aims to develop a learning media called Sammelnalbum that utilizes barcode technology to enhance listening skills in filling in the blanks in German sentences among eleventh-grade high school students. This study employs the Research and Development (R&D) model, which includes steps such as identifying potential issues, data collection, product design, and design validation. The validation results indicate that the developed media received a score of 84% for material validation and 97.5% for media validation, indicating that it is suitable for use without the need for revisions. This media is designed to meet the needs of students in the digital age, integrating relevant technology. It is hoped that the use of Sammelnalbum with barcodes can provide an effective alternative in language learning and encourage the development of learning media for other skills. This research contributes significantly to both teachers and students in improving German language learning outcomes at the high school level.